VIABILITAS RAGAM HIAS SULUR-GELUNG - Agung Wicaksono; Akhmad Nizam (Corak : Jurnal Seni Kriya, 2016)
Motive of ukel, lung or plant tendrils (forming like question mark) spiraling inside andoutside is named sulur gelung ornament. These ornaments are often found in Hinduism andBudhist temples even in the mosque with particular style. Sulur gelung ornament has to befondness for people when we look at the craft as visual art. Many artefacs of heritage oftenvisualized form of lung or ukel. In javanese fashion ukel as trendil of hair fastened by ukel konde.Ukel konde is used for make up on the face also for forming of puppet’s hair and isen-isen, evenfor forming of punokawan’s hair (Semar, Gareng, Petruk, and Bagong). Form like ukel is alsofound in the architecture of mosque especially on the mihrab or altar, we can also be found inthe architecture of javanese traditional house. The temples of Hinduism and Budhist in Javahave ornament of sulur gelung, for example Candi Gondosuli, Candi Gedongsongo, CandiKalasan, candi Prambanan, Candi Sewu, Candi Lumbung, and many of temples in East Java.Is this ornament comes from India through the Hinduism or Hinduism-Budhist diffusionto Java? Or possibly this is an original local archetype of java or is this the result of aculturationof Hinduism-Budhist, Java, and Islam ? This reaserch will review the sulur gelung ornamentprovenience which is commonly using as fix pattern and the spirit or viability of javanese style.The sulur gelung ornament has evoluted since Hinduism-Budhist until Islamic diffusion asreception religion in the culture. Key wors : aculturation, ornament, sulur-gelung